Racquet Club Cottages West, floor and plot plan [front and back] - William F. Cody::::::::: (1950)
Front of fold out map brochure illustrating a plot plan for the Racquet Club Cottages designed by William F. Cody. Back of fold out map brochure illustrates alternative floor plans for the Racquet Club Cottages designed by William F. Cody.